Super VGA Graphics / Programming Secrets - Rimmer Steve (Windcrest/ Mcgraw-Hill, 1993)
Learn how to write graphics-based software that will dazzle your users. Preface, Birds and Martians and Flying Pigs, Graphic Files, 16-Color Graphics, 256-Color Graphics, High-Color Graphics, Display Fonts, Printing Super VGA Graphics, Writing Animated Games, Detecting Super VGA Cards, Index.